Communication Strategy of Directorate General of Immigration in Socializing electronic Visa on Arrival (e-VOA) to Foreign Citizens - Tiominar, Irnadika Natasia; Astuti, Arum Widya; Hanuransyah, Melanie Rizky (PERSPEKTIF, 2024)
The Electronic Visa on Arrival (e-VOA) represents one of the immigration products introduced by the Directorate General of Immigration in response to the COVID-19 pandemic, serving as a measure to bolster digital immigration services. As the primary beneficiaries of the e-VOA are foreign nationals, effectively disseminating information to this target demographic presents a challenge for the Public Relations division of the Directorate General of Immigration. This study endeavors to assess the implementation of the ROPE stages within the communication strategy employed by the Public Relations department to promote e-VOA among foreign nationals. Employing a qualitative research methodology with a descriptive approach, the study utilizes the ROPE PR planning model as its conceptual framework. ROPE is a public relations planning model that consists of four main stages: Research, Objectives, Programming, and Evaluation. The research stage involves gathering information about the organisation, the issue at hand, and the public being targeted for communication. After that, the objectives stage sets clear campaign objectives to address the identified problem. Then, the programming stage involves planning and implementing the steps necessary to achieve the objectives, including the use of effective media and communication strategies. Finally, the evaluation stage assesses the success of the programme by gathering feedback and measuring the achievement of the set objectives.  This research shows that the communication strategy adopted by the Directorate General of Immigration in the socialisation of e-VOA achieved an effectiveness level of around 75%, based on the Community Satisfaction Index (SSI) which shows that many respondents felt well informed. The research findings indicate that the Public Relations division of the Directorate General of Immigration has adopted structured measures incorporating well-defined ROPE stages in their execution of e-VOA socialization activities. Nonetheless, challenges persist during these socialization endeavors, including constraints related to budgetary limitations, human resources, and media outreach. The results of this study provide important insights for the Directorate General of Immigration to improve future communication strategies, by designing campaigns that are more targeted and responsive to public needs, and utilising feedback to improve the communication process and increase public satisfaction.